SOCIAL, MEDICAL AND EPIDEMIOLOGICAL FACTORS AFFECTING THE PREVALENCE OF TUBERCULOSIS AND THEIR PROGNOSIS (Eureka Journal of Health Sciences & Medical Innovation, 2026)
The spread of tuberculosis is shaped by the complex and interrelated effects of social, medical, and epidemiological factors. This study analyzes the main social determinants influencing the spread of tuberculosis, including poverty, migration, living conditions, malnutrition, and issues of social stigma. In addition, the epidemiological significance of medical factors such as HIV infection, chronic noncommunicable diseases, harmful habits, and drug-resistant forms of tuberculosis is highlighted. Among epidemiological factors, the spread of infection in closed institutions, delayed diagnosis, subclinical forms of tuberculosis, and the impact of disruptions in the healthcare system during pandemic conditions are examined. The study substantiates the importance of using modern epidemiological and mathematical modeling methods in forecasting the spread of tuberculosis, noting that these approaches serve as an important scientific basis for planning preventive measures and strengthening disease control.
Keywords: Tuberculosis, epidemiology, TB/HIV coinfection, drug-resistant tuberculosis, migration, closed institutions, delayed diagnosis, epidemiological forecasting.